OPTMALISASI KEMAMPUAN DAERAH KABUPATEN/KOTA DALAM MELAKSANAKAN OTONOMI DAERAH - Mulatto Mulatto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2004)
The new paradigm on administration in Indonesia has been changed from centralization to the desentralization. Local government has authority fully to manage their autonomy. The objective of this research are to analyze and to know how high the capacity of the Regency/Cities in establishing local autonomy. For knowing the capacity of Regencies/Cities, we have taken a grounded method and used 7 variables consist of authority, institution, manpower, infrastructure, economy, people participation, and public service. The result of this research are: (I) There are 8 Regencies/Cities experience have Jess capacity than before and 4 Regencies/Cities are better capacity (2) The Regencies/Cities still depend on Central government in financing their activities for establishing their authority.